Change-Point Analysis: An Effective Technique for Detecting Abrupt Change in the Homicide Trends in a Democratic South Africa - P. Monyeki; N. Naicker; I. C. Obagbuwa (The Scientific World Journal)
South Africa is considered the murder capital of the world. The challenge for the South African government is to attract foreign investment to boost the economy in a country plagued by homicide. In this study, a change-point analysis was used to pinpoint significant changes in the murder trends in each of the nine provinces in South Africa from 2005 to 2015. This analysis will assist authorities to gain a better understanding of the big picture view in order to mitigate against this crime. Two methods were used in the analysis, namely, CUSUM and Bootstrap. CUSUM was used to analyse data trends, and Bootstrap was used to calculate the occurrence of change points based on the confidence level. The results of the analysis clearly show the abrupt shifts in murder data across the provinces of South Africa. In addition, we used the South African population statistic dataset from 2005 to 2015 to evaluate the relationship between population of the nine provinces and contextualise the murder crime rates year to year and province to province.